MINAT SISWI PUTRI SMP 34 PEKANBARU TERHADAP MATA PELAJARAN PENJASORKES - Aryadi, Diki; Wijayanti, Ni Putu Nita; Syahriadi, Syahriadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: The purpose of this study was to find out how much interest female students at SMP Negeri 34 Pekanbaru have in physical education subjects. This type of research is classified as descriptive, namely to reveal the problem as it is. This research was conducted on female students at SMP Negeri 34 Pekanbaru. In January-June 2023. Based on the results of research on female students' interest in learning physical education at SMP Negeri 34 Pekanbaru, the following conclusions can be drawn: The ability level of female students' interest is 80.74%, meaning that the level of female students' motivational ability to modify Physical Education learning in SMP Negeri 34 Pekanbaru, is in a good classification. The level of ability for the role of the physical education teacher at SMP Negeri 34 Pekanbaru is 78.63%, meaning that the level of ability for the role of the physical education teacher at SMP Negeri 34 Pekanbaru is in a good classification. The ability level for Physical Education facilities and infrastructure at SMP Negeri 34 Pekanbaru is 65.61%, meaning that the level of capability for Physical Education facilities and infrastructure at SMP Negeri 34 Pekanbaru is in a good classification.Key Words: Interest, Physical Education Lesson